Aggregate shocks or aggregate information? Costly information and business cycle comovement - Laura Veldkamp; Justin Wolfers (Institute for the Study of Labor (IZA), 2006)
When similar patterns of expansion and contraction are observed across sectors, we call this a business cycle. Yet explaining the similarity and synchronization of these cycles across industries remains a puzzle. Whereas output growth across industries is highly correlated, identifiable shocks, like shocks to productivity, are far less correlated. While previous work has examined complementarities in production, we propose that sectors make similar input decisions because of complementarities in information acquisition. Because information about driving forces has a high fixed cost of production and a low marginal cost of replication, it can be more efficient for firms to share the cost of discovering common shocks than to invest in uncovering detailed sectoral information. Firms basing their decisions on this common information make highly correlated production choices. This mechanism amplifies the effects of common shocks, relative to sectoral shocks.
urn:nbn:de:101:1-20090825218
Keywords: 330; Branchenkonjunktur; Trend; Produktion; Produktivität; Informationsverhalten; Produktionsplanung; Wirtschaftsmodell